The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s40780-022-00251-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of risk factors for acute kidney injury among inpatients administered sulfamethoxazole/trimethoprim: a retrospective observational study

Abstract: Background Sulfamethoxazole/trimethoprim (SMX/TMP) potentially increases the serum creatinine levels, resulting in acute kidney injury (AKI). However, the clinical characteristics of the AKI associated with SMX/TMP and the risk factors for its development have not been fully characterized. Methods A retrospective cohort observational analysis was conducted on adult inpatients who started SMX/TMP treatment at the Tokyo Women’s Medical University, Ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
1
4
1
Order By: Relevance
“…The cohort consisted mainly of elderly patients, frequently hypertensive, which aligns with findings from previous studies 12 , 13 , 34 . All patients in our study were immunocompromised, a condition leading to confirmed or suspected opportunistic infections that required SMX therapy.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The cohort consisted mainly of elderly patients, frequently hypertensive, which aligns with findings from previous studies 12 , 13 , 34 . All patients in our study were immunocompromised, a condition leading to confirmed or suspected opportunistic infections that required SMX therapy.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, the median time to onset of AKI after SMX introduction was 4 days (IQR 3.5–5 days), shorter than in Fraser’s study (6.5 days) and Shimizu’s study (8 days [IQR, 5–16 days]) 12 , 13 .…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations